2019
DOI: 10.15537/smj.2019.1.23370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immediate versus delayed loadings of dental implants on the oral health-related quality of life in Saudi population

Abstract: Objectives: To assess the effects of immediate and delayed loadings of dental implants on the overall quality of life (QoL) of patients. Methods: The prospective analysis was conducted in the Department of Periodontology Clinics, Faculty of Dentistry Hospital, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia. The study was conducted from November 2013 to August 2016 and was according to the principles of the Helsinki Declaration. Quality of life in 24 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…The factors that impact self-reported oral health are not well understood, but it has been suggested that oral diseases have a negative impact on self-reported oral health, and that this impact is worse at younger ages ( Slade and Sanders, 2011 ). Several researchers evaluated OHRQoL in young adult subjects in Australia ( Brennan and Spencer, 2009 ), Tanzania ( Masalu and Astrøm, 2002 ), Japan ( Yamane-Takeuchi et al, 2016 ), Malaysia ( Masood et al, 2013 ), Sweden ( Oscarson et al, 2007 ), Korea ( Choi et al, 2015 ), and Saudi Arabia ( Bahammam and Fareed, 2019 ). To summarize, OHRQoL in young adults was affected by education ( Masalu and Astrøm, 2002 , Masood et al, 2013 ), negative life experience ( Brennan and Spencer, 2009 ), pain ( Yamane-Takeuchi et al, 2016 ), and self-reported oral health ( Masalu and Astrøm, 2002 , Yamane-Takeuchi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors that impact self-reported oral health are not well understood, but it has been suggested that oral diseases have a negative impact on self-reported oral health, and that this impact is worse at younger ages ( Slade and Sanders, 2011 ). Several researchers evaluated OHRQoL in young adult subjects in Australia ( Brennan and Spencer, 2009 ), Tanzania ( Masalu and Astrøm, 2002 ), Japan ( Yamane-Takeuchi et al, 2016 ), Malaysia ( Masood et al, 2013 ), Sweden ( Oscarson et al, 2007 ), Korea ( Choi et al, 2015 ), and Saudi Arabia ( Bahammam and Fareed, 2019 ). To summarize, OHRQoL in young adults was affected by education ( Masalu and Astrøm, 2002 , Masood et al, 2013 ), negative life experience ( Brennan and Spencer, 2009 ), pain ( Yamane-Takeuchi et al, 2016 ), and self-reported oral health ( Masalu and Astrøm, 2002 , Yamane-Takeuchi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were conducted in Saudi Arabia to quantify the impact of malocclusion, general anesthesia, periodontitis, complete denture, full mouth rehabilitation, previous dental experience, and fear among children and guardians of autistic children on OHRQoL ( AlBaker, 2013 , Alghamdi et al, 2017 , Baghdadi and Muhajarine, 2015 , Baghdadi, 2014 , Bahammam and Fareed, 2019 , Dawoodbhoy et al, 2013 , El-Meligy et al, 2016 , Hassan and Amin, 2010 , Merdad and El-Housseiny, 2017 , Pani et al, 2013 ), but no study has been conducted to address the effect of dental decay or caries experience on the OHRQoL of adults in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the effect of immediate and delayed implant loading into the extracted site on the QoL in pre- and post-insertion period. QoL was better among the patients where dental implants were loaded immediately as compared to the delayed loading of dental implant [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is considered to have a great prospect of implant surgery. [10][11][12][13] However, there are many problems such as insufficient bone mass in immediate implantation, so finding suitable bone grafting materials has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%